Parametric studies on in situ transesterification of palm fruit and waste mesocarp for biodiesel production - Baharuddin, Akmal; Zakaria, Rabitah (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Transesterification of vegetable oil is the most common method used for biodiesel production. However, a new technique known as “reactive extraction” or “in situ transesterification” can simplify the process and has the potential to reduce the production cost. The potential of biodiesel production from fresh palm fruit and waste mesocarp using this technique has been investigated. Parametric studies were conducted to evaluate the effects of solvent to oil molar ratio, catalyst concentration and temperature on the yield and the reaction rate. Sodium hydroxide was used in this study. A high yield of ester (> 25.99% and >13.99%) was achieved at high solvent to oil molar ratios (400:1 and 500:1) for mesocarp fruit and waste mesocarp respectively. High ester yield can be obtained by using high catalyst concentration (0.15 molal) for both palm fruit and waste mesocarp (34.2% and 13%). Temperature plays an important role in this process since higher temperature give higher ester yield.